From the bench to clinical practice: understanding the challenges and uncertainties in immunogenicity testing for biopharmaceuticals. (19th January 2016) - Gunn, G R; Sealey, D C F; Jamali, F; Meibohm, B; Ghosh, S; Shankar, G
Summary: Unlike conventional chemical drugs where immunogenicity typically does not occur, the development of anti-drug antibodies following treatment with biologics has led to concerns about their impact on clinical safety and efficacy. Hence the elucidation of the immunogenicity of biologics is required for drug approval by health regulatory authorities worldwide. Published ADA 'incidence' rates can vary greatly between same-class products and different patient populations. Such differences are due to disparate bioanalytical methods and interpretation approaches, as well as a plethora of product-specific and patient-specific factors that are not fully understood. Therefore, the incidence of ADA and their association with clinical consequences cannot be generalized across products. In this context, the intent of this review article is to discuss the complex nature of ADA and key nuances of the methodologies used for immunogenicity assessments, and to dispel some fallacies and myths.